Strategi Bisnis Thrifting @ngebedje_store di Palembang - Utami, Elvira Putri; Hasmawati, Fifi; Manalullaili (Pubmedia Social Sciences and Humanities, 2024)
The research is motivated by the thrifting business which is experiencing significant growth in Indonesia because the cheap, unique and quality prices offered by thrift shops have become an attractive alternative for shoppers on a limited budget. However, the thrift business is faced with the challenge of competition and the ban on imports of used clothing in Indonesia, which has had a negative impact on thrift traders. Therefore, this research aims to investigate the thrift business strategy carried out by @Ngebedje_store. The research method used is descriptive qualitative with data collection through observation, interviews and documentation. In this research, Promotion Mix theory such as Advertising, Sales Promotion, Publicity and Personal Selling is applied to evaluate the effectiveness of the promotional strategy implemented by Ngebedje Store. The research results show that Ngebedje Store has succeeded in implementing the four elements of the promotional mix well. This strategy has increased customer interest in the products offered, resulting in increased sales, as well as growth in the number of followers on his Instagram account. Apart from that, Ngebedje Store has also succeeded in maintaining customer loyalty by fostering trust, maintaining satisfaction and maintaining good relationships with customers. This ultimately made Ngebedje Store able to survive and compete in the thrift industry in Palembang.